Supplementation of Lactocbacillus acidophilus SNP-2 Into Tape and its Effect to the Volunteer - Endang S Rahayu; Siti N Purwandhani (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2004)
Functional food is defined as any potentially healthful food or food ingredient that may provide a health benefit beyond the traditional nutrients it contains. Many researches have been conducted on the health benefit of probiotic (life bacterial cells), one of the ingredient of functional foods. One of the potential bacteria used for probiotic agent and also involved in traditional fermented foods are lactic acid bacteria (LAB). Previous research showed that Lactobacillus acidophilus SNP-2 isolated from faecal material of healthy infant is resistant to acid and bile salt, and has an antagonistic effect against several enteric bacterial pathogens. The objective of this research was to study the effect of L. acidophilus SNP-2 as probiotic agent to the health benefits. These bacteria were supplemented into tape ketan (fermented sticky rice), the indigenous Indonesian fermented food. Tape ketan was chosen as the carrier of probiotic biomass based on the high population of LAB in this product, i.e., 1.3 x 108 CFU/g. Addition of L. acidophilus SNP-2 biomass prior to fermentation of tape ketan resulted in a higher total of LAB cells, i.e. 2.1 x 109 CFU/g compared to the amount of 1.5 x 108 CFU/g when the addition was done after fermentation. Consumption of tape ketan containing probiotic agent by the volunteers increased the population of lactobacilli (from 1.7x107 CFU/g to 9.9x107 CFU/g) and decreased the population of enterobacteriacea (from 5.4x109 CFU/g to 4.4x108) in their faecal material. This phenomenon revealed that probiotic agent was able to colonize and inhibit the growth of enterobacteriaceae in the gastrointestinal tract. The result implied that tape ketan can be used as a carrier for probiotic agent and it can be categorized as functional food. Key words : Tape ketan, lactobacillus acidophilus, probiotic.